(Paleo)glacier studies in Patagonia over the past decades (1976–2020): A bibliometric perspective based on the Web of Science. (February 2023) - Soteres, Rodrigo L.; Riquelme, Fabián M.; Sagredo, Esteban A.; Kaplan, Michael R.
Abstract: Patagonia features the most extensive glaciers of the Southern Hemisphere, excluding Antarctica, and a vast inventory of glacial landforms, so it is thought to have played a key role in (paleo)glacier studies since the late 19th century. However, no systematic attempts to characterize the specific research trends and the scientific community focused on Patagonian cryosphere have been conducted so far. To fill this gap, we analyzed the metadata associated to 305 articles compiled from the Web of Science database following a bibliometric approach covering the period between 1976 and 2020. Our results point to an irregular but net increase on the number of contributions on Patagonian (paleo)glaciers. Mass balance analyses based on satellite data of present-day glaciers and the reconstruction of past glacier activity by dating glacial landforms formed during the Last Glacial Termination, were the most addressed topics during the analyzed period. Patagonian (paleo)glacier studies are mostly published in generic Earth Sciences publications, followed by Quaternary and glaciological journals. Most of the studies were led by scientists from the United Kingdom, followed by Chile, Argentina and United States. In terms of collaborations, these studies can be divided into two main clusters, one composed by researchers from United States, Chile and Argentina institutions, and another mostly composed by British researchers. So far, the most prolific authors are nearly equally distributed in nationality, yet gender inclusion and international collaborations are still caveats that must be solved. Even though our query on the Web of Science missed highly influential (so-called) grey literature, such as local scientific journals and technical reports, the reviewed scientific literature unambiguously indicates that Patagonia is a privileged location for (paleo)glaciers studies worldwide and that it will continue offering vast opportunities to tackle critical questions related to global cryosphere and past-to-present climate changes. Highlights: Patagonia is a privilege site for studying present and past glacier dynamics and the evolution of climate changes at hemispheric and global scale. Glacier dynamics during the 20 th century and and the Last Glacial Termination are the most common topics addressed in past decades in the WOS. Patagonian (paleo)glacier studies has contributed to the development or improvement of diverse analytical techniques. United Kingdom, United States, Chile and Argentina produced the largest number of WOS-listed papers on (paleo)glaciers in past decades. The related scientific community is fairly heterogeneous. Although, inclusion and international collaboration issues still need to improve.